THE INFLUENCE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMEN ON EMPLOYEE PERFORMANCE IN HOTEL SANTIKA PONTIANAK - Hinur, Annadi Hinur B11111140 (Jurnal Manajemen Update, 2018)
The research objective was to dertmine the influence of organizational culture and organizational commitment to employee performance Santika Hotel Pontianak Partially. This research is an explanatory survey research. Data collected from all employees of santika hotel PontianakÂ  as much as 65 respondents, data collection though questionnarre, the technique of data analysis using multiple linear regression analysis. Result of research indicate that organizational culture have positive and significant influence to employee performance and organizational commitment have a positive and signifikan effect on employee performance.Â Keywords : organizational culture, organizational commitmen and employees performance